Analisis Pengaruh Jenis dan Intensitas Suara Terhadap Kemampuan Memori Jangka Pendek, Tingkat Kantuk, dan Kecepatan Denyut Jantung Mahasiswa dalam Kegiatan Menghafal - Vania, Grace; Soesilo, Novi; Sarvia, Elty (Jurnal Optimalisasi, 2024)
In the process of learning, having good memory skills is crucial for students. Several factors can affect memory, one of which is an external factor, sound. Sound distraction can disrupt concentration, speed up the pulse rate, and cause sleepiness, but on the other hand, it can also eliminate sleepiness. This research aims to analyze the effect of type and intensity of sound on college students' short-term memory abilities, sleepiness level, and heart rate, analyze the relationship between these variables, and provide suggestions for a conducive learning environment. This research was conducted in a laboratory using Task Short-Term Memory, the Stanford Sleepiness Scale, and an oximeter. The data collected will be processed using ANOVA and Pearson Correlation Tests. The results indicated that the type of sound (preferred music and crowd noise) and sound intensity (±50 dB and ±70 dB) do not affect short-term memory ability, sleepiness level, and heart rate. Furthermore, sleepiness level has a negative correlation with heart rate. Based on the findings, the optimal learning environment suggested for college students is music with a preferred intensity of ±50 dB. In contrast, the worst learning environment is a crowded environment, such as a café.